2012
DOI: 10.1021/jp208596e
|View full text |Cite
|
Sign up to set email alerts
|

Grand Canonical Monte Carlo Simulation of Low-Pressure Methane Adsorption in Nanoporous Framework Materials for Sensing Applications

Abstract: Although the properties of nanoporous framework materials (NFMs) for high-pressure gas storage are well-known, low-level gas detection (<5 mbar) is also possible. Here, we describe a systematic investigation of NFM structure to identify advantageous features for methane sensing. Using grand canonical Monte Carlo simulations, we show that trends at low pressures relevant to sensing do not fully mirror those at high pressures. NFMs with pore diameters similar in size to methane show the highest uptake, and amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 84 publications
1
42
0
Order By: Relevance
“…For comparison, the maximum methane Q st value from the CNT simulations (45.1 kJ mol 21 ) is significantly larger than the value of 21.0 kJ mol 21 obtained from a computational screening of MOF structures [19] but only slightly larger than the maximum value obtained from a computational screening of methane adsorption in hypothetical MOFs. [52] Comparing maximum Q st values from hypothetical MOFs and CNTs helps to identify desired pore geometries of potential adsorbents in the absence of unusually strong guest -host interactions (e.g.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…For comparison, the maximum methane Q st value from the CNT simulations (45.1 kJ mol 21 ) is significantly larger than the value of 21.0 kJ mol 21 obtained from a computational screening of MOF structures [19] but only slightly larger than the maximum value obtained from a computational screening of methane adsorption in hypothetical MOFs. [52] Comparing maximum Q st values from hypothetical MOFs and CNTs helps to identify desired pore geometries of potential adsorbents in the absence of unusually strong guest -host interactions (e.g.…”
Section: Resultsmentioning
confidence: 66%
“…argon, methane), the relationship between pore size and kinetic diameter has already been shown. [18,19,56] By orienting the bond axis parallel to the nanotube, diatomic molecules considered here (N 2 and O 2 ) can access pores much smaller than their kinetic diameters. This finding provides potential new options for gas separation involving diatomic molecules based on very restricted diffusion pathways or pore diameters.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the structure of the as-created MOF, in which H 2 O molecules are coordinated to the metal sites. Experimental 23,61 and theoretical 8,62 studies have also shown that initial H 2 O uptake begins at the metal centers of Cu-BTC. This behavior has been attributed to the relative hydrophobicity of pores due to the linker chemistry.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Karra et al [24] investigated the influence of open metal sites in HKUST-1 onto the selectivity between CO and CH 4 , and they found that the main pore size was large enough to hold both molecules. Zeitler et al [20] conducted a GCMC simulation of nano-porous frameworks including HKUST-1, at low pressure CH 4 adsorption.…”
Section: Introductionmentioning
confidence: 99%